The role of crowdion mass transfer in relaxation processes near hard concentrators - Kononenko, V.G.; Bogdanov, V.V.; Turenko, A.N.; Volosyuk, М.А.; Volosyuk, А.V.; Karazin, V.N. (Вопросы атомной науки и техники, 2016)
Mechanisms of stress relaxation in KCl single crystals around hard corundum inclusions have been studied. The samples for the investigation were prepared by alloying the corundum balls into the single crystal. During the subsequent cooling of the system from the crystal melting point (1049 К) to room temperature (293 К), the ball indentation of the crystal was carried out. Dislocation structures around the balls of different sizes (from 2 to 20 m) were analyzed at various cooling temperatures (cooling times were from 2 to 708 min). It has been shown that the observed number of dislocation loops (taking into account their diffusion dissolving under cooling) has transferred not more than a half of the total dilatation volume. In this connection it is assumed that not less than a half of the mass transfer process is realized by a crowdion mechanism.